Efficacy of "groundnut oil" and "coconut oil" as a substitute for "xylene" in clearing tissues samples - A comparative study - Priyadharshini Saravanakumar; R Bharanidharan; Ramya Ramadoss; Aravind; A Ramesh Kumar (Wolters Kluwer Medknow Publications, 2019)
Background: Since yore, "xylene" has always been the nonpareil clearing medium known to be employed in tissue processing and staining. However, the toxic effects of "xylene" range from mild irritation to its severe form as a carcinogenic agent. As there is an increasing need for replacement of this perilous agent, this study aims to determine the efficacy of "pure groundnut oil" (GO) and "pure coconut oil" (CO) which are indigenous to us, as an option in contrast to "xylene" as a clearing agent. Materials and Methods: An aggregate of 45 delicate tissue samples were handled at the same time in "xylene" (15) "pure GO" (15), and "pure CO" (15) as clearing specialists. The "xylene-" treated samples (X), "pure CO-" treated samples, and "pure GO-" treated samples were inspected for cellular architecture and quality of staining and comparison has been made between the three groups. Results: All the three groups showed similar results, and there was no difference identified when checked for cellular architecture and staining quality. Conclusion: The results suggest that both "pure CO" and "pure GO" has been shown to be an efficient replacement for "xylene" as a clearing medium, without jeopardizing on its histological features.